2022
DOI: 10.3389/fmicb.2022.800061
|View full text |Cite
|
Sign up to set email alerts
|

Environment and Co-occurring Native Mussel Species, but Not Host Genetics, Impact the Microbiome of a Freshwater Invasive Species (Corbicula fluminea)

Abstract: The Asian clam Corbicula fluminea (Family: Cyneridae) has aggressively invaded freshwater habitats worldwide, resulting in dramatic ecological changes and declines of native bivalves such as freshwater mussels (Family: Unionidae), one of the most imperiled faunal groups. Despite increases in our knowledge of invasive C. fluminea biology, little is known of how intrinsic and extrinsic factors, including co-occurring native species, influence its microbiome. We investigated the gut bacterial microbiome across ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 74 publications
3
12
0
Order By: Relevance
“…Stevick et al (2021) observed that the gut microbiomes of non‐depurated C. virginica vary spatially over their range in Narragansett Bay with important covarying environmental factors such as temperature, salinity, dissolved oxygen and nutrients. Similar effects of the site have been observed in the gut microbiomes of non‐depurated freshwater bivalves (Chiarello et al, 2022; Lawson et al, 2022). The gut microbiomes of non‐depurated bivalves have also been demonstrated to vary temporally over both years (McCauley et al, 2021) and seasons (Akter et al, 2023; Conceição et al, 2021).…”
Section: Discussionsupporting
confidence: 73%
“…Stevick et al (2021) observed that the gut microbiomes of non‐depurated C. virginica vary spatially over their range in Narragansett Bay with important covarying environmental factors such as temperature, salinity, dissolved oxygen and nutrients. Similar effects of the site have been observed in the gut microbiomes of non‐depurated freshwater bivalves (Chiarello et al, 2022; Lawson et al, 2022). The gut microbiomes of non‐depurated bivalves have also been demonstrated to vary temporally over both years (McCauley et al, 2021) and seasons (Akter et al, 2023; Conceição et al, 2021).…”
Section: Discussionsupporting
confidence: 73%
“…For example, another study of Corbicula habitat preference in the River Minho estuary in Spain showed a positive relationship with Corbicula biomass and the organic matter (OM) content of the sediment (Sousa et al, 2008), but did not mention the presence of mussels. Sediment organic matter produced by mussels via biodeposition may be an important factor influencing the distribution of Corbicula , because OM can be an alternative food source that is accessed through pedal feeding (Hakenkamp & Palmer, 1999; Hakenkamp et al, 2001) and may provide them with beneficial gut microbiota (Chiarello et al, 2022). It seems likely high densities of Corbicula may be supported in habitats with high organic matter content, such as mussel beds (Atkinson & Forshay, 2022; Vaughn & Hakenkamp, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Benthic characteristics are an important factor in the distribution of benthic species, including mussels and Corbicula which live buried in benthic habitats and therefore may partition habitat at fine spatial scales. We hypothesized increasing probability of Corbicula occurrence and density in habitats where mussels already exist if habitat requirements OM can be an alternative food source that is accessed through pedal feeding (Hakenkamp & Palmer, 1999;Hakenkamp et al, 2001) and may provide them with beneficial gut microbiota (Chiarello et al, 2022). It seems likely high densities of Corbicula may be supported in habitats with high organic matter content, such as mussel beds (Atkinson & Forshay, 2022;Vaughn & Hakenkamp, 2001).…”
Section: Sity Interestingly Most Research Addressing Interactions Bet...mentioning
confidence: 99%
“…For population genetics analyses, a subset of individuals (23 species, 3–15 individuals per site per species for species present at a given site) were collected during the quantitative and/or opportunistic sampling and brought back to laboratory on ice where they were flash frozen and stored at −80°C (Chiarello et al, 2022). Mantle tissues were subsequently clipped from partially thawed mussels and stored in molecular grade absolute ethanol at −80°C prior to DNA isolation using Qiagen DNeasy kits (Germantown, Maryland).…”
Section: Methodsmentioning
confidence: 99%